2021
DOI: 10.1186/s12909-021-02605-y
|View full text |Cite
|
Sign up to set email alerts
|

Exploring why medical students still feel underprepared for clinical practice: a qualitative analysis of an authentic on‐call simulation

Abstract: Background Current research shows that many UK medical graduates continue to feel underprepared to work as a junior doctor. Most research in this field has focused on new graduates and employed the use of retrospective self-rating questionnaires. There remains a lack of detailed understanding of the challenges encountered in preparing for clinical practice, specifically those faced by medical students, where relevant educational interventions could have a significant impact. Through use of a no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 15 publications
0
16
0
Order By: Relevance
“…We investigated the learning outcomes of 400 undergraduates in Dalian Medical University who were taught under this teaching mode. Our results show that students' mastery of the content and, more importantly, their hands-on skills are improved under this model, which better supports their challenging transition from medical students to junior doctors and beyond [17] . Abbreviations ICC: immunocytochemistry; q-PCR: quantitative real time polymerase chain reaction.…”
Section: Discussionmentioning
confidence: 54%
“…We investigated the learning outcomes of 400 undergraduates in Dalian Medical University who were taught under this teaching mode. Our results show that students' mastery of the content and, more importantly, their hands-on skills are improved under this model, which better supports their challenging transition from medical students to junior doctors and beyond [17] . Abbreviations ICC: immunocytochemistry; q-PCR: quantitative real time polymerase chain reaction.…”
Section: Discussionmentioning
confidence: 54%
“…We investigated the learning outcomes of the undergraduate students in DMU who were instructed under this teaching model. Our findings revealed that the students' mastery of the course and, more importantly, their practical skills improved under this model, which better supports their challenging transition from medical students to junior doctors and beyond 32 . However, there are certain limitations in developing effective curriculums for students and training teachers to effectively utilize digital teaching techniques.…”
Section: Discussionmentioning
confidence: 66%
“…Our findings revealed that the students' mastery of the course and, more importantly, their practical skills improved under this model, which better supports their challenging transition from medical students to junior doctors and beyond. 32 However, there are certain limitations in developing effective curriculums for students and training teachers to effectively utilize digital teaching techniques. As the pandemic continues to spread, the importance of hybrid learning comes to the forefront.…”
Section: Discussionmentioning
confidence: 99%
“…With negative IPC outcomes, junior doctors' strong negative emotions isolated them in a selfcentred rumination process that prevented them from learning from other team members. 42,43 By judging the value of a collaboration by its outcome, also called outcome bias, junior doctors made an inference regarding the collaboration only based on the outcome rather than evaluating the whole collaboration with all its information. 44,45 A curriculum focused on workplace learning should provide two types of formal reflective spaces for junior doctors: one space for discussing IPC independent of the clinical outcome being good or bad, to help junior doctors create the habit of reflecting on teamwork and awareness of how their perception of teamwork can be influenced by the context in which it takes place.…”
Section: Discussionmentioning
confidence: 99%
“…With negative IPC outcomes, junior doctors' strong negative emotions isolated them in a self‐centred rumination process that prevented them from learning from other team members. 42 , 43 By judging the value of a collaboration by its outcome, also called outcome bias , junior doctors made an inference regarding the collaboration only based on the outcome rather than evaluating the whole collaboration with all its information. 44 , 45 …”
Section: Discussionmentioning
confidence: 99%